Improving the care of children with urinary tract infection: use of a clinical decision proforma. Issue 1 (22nd April 2015) - Leach, Daniel
Abstract: Urinary tract infection (UTI) is a common and important clinical problem in children. Follow up imaging is indicated in some cases to reduce the risk of long-term harm from UTI and sometimes to help guide acute management. Overuse of imaging may be harmful due to radiation exposure, as well as increasing demand on services and budgets. On the other hand under-use of imaging may leave children vulnerable to renal damage and long-term morbidity. Accepted standards propose an imaging strategy specific to age and type of UTI. The complexity of the guideline makes compliance with the standards challenging. The aim of this project was to assess current practice for imaging of children with UTI managed at The Royal Oldham Hospital and to improve compliance with accepted standards through the use of a proforma to aid clinical decision making, supported by an education programme. A retrospective audit was performed over a 6 month period both prior to and after the intervention. The baseline audit found 57.7% of children treated for UTI (n=26) had imaging compliant with the accepted standards, which improved to 75.9% (n=29) on post-measurement. The percentage of inappropriate investigations reduced from 52.4% to 10.5%. The percentage of missed investigations reduced from 35.0% to 32.0%. The proforma was used and filed in 40% of cases where practice was in line with accepted standards. It was not used in any of the cases where practice deviated. In conclusion, a clear clinical decision aid, supported by an education programme, can significantly improve compliance with accepted standards for imaging of children with UTI. This may also be transferable to other scenarios where guidelines exist but have reduced efficacy due to complexity and/or lack of understanding.